Discovery of novel quaternary ammonium derivatives of (3R)-quinuclidinyl amides as potent and long acting muscarinic antagonists. Issue 8 (15th April 2015) - Prat, Maria; Buil, María Antonia; Fernández, Maria Dolors; Tort, Laia; Monleón, Juan Manuel; Casals, Gaspar; Ferrer, Manuel; Castro, Jordi; Gavaldà, Amadeu; Miralpeix, Montserrat; Ramos, Israel; Vilella, Dolors; et al.
Graphical abstract SAR around R1, R2 and R3 are reported.